Yasuo Wakatsuki e Iyo Kunimoto, (eds.). La inmigración japonesa en Bolivia. Estudios históricos y socioeconómicos. Universidad de Chuo, Tokio, 1985. 243 pp. - Ota Mishima, Ma. Elena (El Colegio de México, 1985)
-